• 809. Упростите выражение: 1)-2(5a-3b)+a; 2)-1,4 (2a-0,3)+0,18; 1 3) - (6а – 1,65) + b; 1 a(3-5b ) + 56 4) a 2 3. .​

Ответы 1

  • Ответ:

    Пошаговое объяснение:-1.

    2(5а-3b) + a = -10a + 6b + a = a - 9b

    2.-1.4(2a - 0.3) + 0.18 = -2.8a + 0.42 + 0.18 = -2.52a + 0.6

    3. -6a + 1.65 - b = -6a - b + 1.65

    4. 3a^2 - 5ab + 56 = 3(a^2 - ab) + 5(a - 2)

    Ответ:

    a - 9b

    -2.52a + 0.6

    -6a - b + 1.65

    3(a^2 - ab) + 5(a - 2).

  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years